Short Communication: Phenotypic diversity of male pelung chickens in West Java Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Asmara IY, Garnida D, Setiawan I, Partasasmita R. 2019. Short Communication: Phenotypic diversity of male pelung chickens in West Java Province, Indonesia. Biodiversitas 20: 2243-2248. Pelung chickens are indigenous chickens from Cianjur District, West Java Province, Indonesia. The male chickens have long and beautiful crowing and have a distinct body figure compared to other indigenous chickens. Chicken contests are conducted regularly as media to show singing ability and body performance of Pelung chickens. Pelung chickens raised in different areas may have different phenotypic characteristics due to keeper preferences. Also, the phenotypic characteristics of the winners of chicken contests may influence keepers to select their chickens. The objective of this study was to determine the phenotypic characteristics of male Pelung Chickens in different areas in West Java, Indonesia. Comb type, as well as the color of eye, beak, skin, plumage, and shank, were recorded in the study. Data were collected through a survey involving 160 male birds in four different districts in West Java Province including Cianjur, Sukabumi, Bandung and Garut Districts. Key informant interview was carried out to support quantitative data. The results showed a limited variation of phenotypic characteristics among male Pelung chickens. Comb type, as well as skin and plumage colors, are criteria to select male Pelung chickens. Phenotypic characteristics of contest winners are also a reference for Pelung keepers in breeding selection.
Keywords: animal genetic resources, conservation, indigenous chickens